The quality, safety, feasibility, and interpretive accuracy of echocardiographic and lung ultrasound assessment of COVID‐19 patients using a hand‐held ultrasound. Issue 7 (6th June 2022) - Dadon, Ziv; Levi, Nir; Alpert, Evan Avraham; Orlev, Amir; Belman, Daniel; Glikson, Michael; Butnaru, Adi; Gottlieb, Shmuel
Abstract: Background: The association between COVID‐19 infection and the cardiovascular system necessitates the use of an echocardiogram in this setting. Information on the utilization, safety, and quality of point‐of‐care cardiac and lung ultrasound using a hand‐held device in these patients is scarce. Aims: To investigate the safety, technical aspects, quality indices, and interpretive accuracy of a hand‐held echocardiogram in patients with COVID‐19. Methods: From April‐28 through July‐27, 2020, consecutive patients with COVID‐19 underwent hand‐held echocardiogram and lung ultrasound evaluation (Vscan Extend™; GE Healthcare) within 48‐h of admission. The operators recorded a series of technical parameters and graded individual experiences. The examinations were further analyzed by a blinded fellowship‐trained echocardiographer for general quality, proper acquisition, and right ventricular (RV) demonstration. Results: Among 103 patients, 66 (64.1%) were male. Twenty‐nine (28.2%) patients could not turn on their left side and 23 (22.3%) could not maintain effective communication. The mean length of each echocardiogram study was 8.5 ± 2.9 min, battery usage was 14 ± 5%, and mean operator‐to‐patient proximity was 59 ± 11 cm. Ninety‐five (92.2%) examinations were graded as fair/good quality. A fair agreement was demonstrated between the operator and the echocardiographer for general ultrasound quality (Kappa = 0.329, p < 0.001). A fair‐good correlation ( r = 0.679, p < 0.001) and substantial agreement (Kappa = 0.612, p < 0.001) were demonstrated between the operator and echocardiographer for left ventricular ejection fraction (LVEF), whereas a fair agreement was demonstrated for RV systolic function (Kappa = 0.308, p = 0.002). LVEF agreement was also assessed using the Bland‐Altman analysis revealing a mean bias of −0.96 (95% limits of agreement 9.43 to −11.35; p = 0.075). Conclusions: Among patients with COVID‐19, echocardiography with a hand‐held ultrasound is a safe and reasonable alternative for a complete formal study (<10% poor‐quality indices). Echocardiogram assessment by the operators during the exam acquisition is reliable for LVEF, while RV systolic function should be subsequently offline reassessed.